State Regulation of the Inshore and Inland Fisheries of Newfoundland: A Study of the Regulatory Role of Federal Fishery Officers - Phyne, John G. (My University, 1988)
This study examines, from a sociological perspective, the relationship between human agency and social structure. It argues that the relatively isolated working conditions of federal fishery officers, based within the inshore fishery of Newfoundland, poses problems stemming from the tension between managerial control and fishery officers' discretionary and incremental policy-making role. These issues are addressed through the street-level bureaucracy perspective and insights from the sociology of organizations. Based upon interviews with fifty-one fishery officers, selected from a population of eighty-five officials, the study argues that: Indirect bureaucratic and technological controls are used to supervise fishery officers' work; despite such controls, these officials have access to discretion, but argue that they use it in order to better implement fishery policies. Finally, these officials have a limited impact upon policy-making within the Department of Fisheries and Oceans. The study concludes by examining the broader context of fishery officers' work in terms of the role of state and Giddens' theory of structuration.
Keywords: Sociology; Sociology